IMPROVING THE OPERATIONS OF SMALL BUSINESS ENTREPRISES TO REDUCE POVERTY - Djalilova, Shaxlo (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
This study investigates strategies to enhance the performance of small business enterprises (SBEs) as a vital approach to poverty reduction. Recognizing the significant role SBEs play in generating employment, income, and stimulating local economic development, the research identifies key challenges that hinder their ability to effectively alleviate poverty. It assesses policy frameworks, financial accessibility, skill development programs, and the adoption of technology as potential avenues to boost their impact. By highlighting successful practices and addressing the barriers faced by SBEs, the study aims to provide actionable recommendations for policymakers and stakeholders seeking to leverage small businesses to improve community well-being and reduce poverty levels.